Perakitan Kultivar Kentang Unggul Indonesia secara Cepat dengan Metode Turunan Klonal Biji Tunggal dan Pra - Evaluasi Secara In Vitro - G. A. Wattimena; Agus Purwito; H . M. Machmud; , Samanhudi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2001)
At least ten years needed to abtain new potato cultivar through sexual hybridization, somatic hybridization or through genetic transformation, To short cut this process, Laboratory of Biotechnology, Department of Agronomy, IPB employed a strategy so called single seed in vitro clonal decent ( SSICD) by usings elected parental lines for TPS (True Potato Seed) production. This breeding consist of in vitro pre evaluation for resistance wilt, fusarium wilt, black leg, rot knot nematode and maturity. Using the same number of bacterial cell / (109 cell/ml), there were positive correlation between in vitro test for disease resistance through dripping test or dripping test with greenhouse test through direct inoculation of Ralstonia solanancearum. Resistant clones to fusarium wilt and verticillium were also resistant to bacterial wilt. In vitro tuberization could be use to evaluate maturity of potato cultivar.   Key words: Potato, SSICD